Normal proliferation and tumorigenesis but impaired pancreatic function in mice lacking the cell cycle regulator sei1. - Pablo J Fernandez-Marcos; Cristina Pantoja; Agueda Gonzalez-Rodriguez; Agueda Gonzalez-Rodriguez; Nicholas Martin; Juana M Flores; Angela M Valverde; Eiji Hara; Manuel Serrano (PLoS ONE)
Sei1 is a positive regulator of proliferation that promotes the assembly of Cdk4-cyclin D complexes and enhances the transcriptional activity of E2f1. The potential oncogenic role of Sei1 is further suggested by its overexpression in various types of human cancers. To study the role of Sei1, we have generated a mouse line deficient for this gene. Sei1-null fibroblasts did not show abnormalities regarding proliferation or susceptibility to neoplastic transformation, nor did we observe defects on Cdk4 complexes or E2f activity. Sei1-null mice were viable, did not present overt pathologies, had a normal lifespan, and had a normal susceptibility to spontaneous and chemically-induced cancer. Pancreatic insulin-producing cells are known to be particularly sensitive to Cdk4-cyclin D and E2f activities, and we have observed that Sei1 is highly expressed in pancreatic islets compared to other tissues. Interestingly, Sei1-null mice present lower number of islets, decreased beta-cell area, impaired insulin secretion, and glucose intolerance. These defects were associated to nuclear accumulation of the cell-cycle inhibitors p21(Cip1) and p27(Kip1) in islet cells. We conclude that Sei1 plays an important role in pancreatic beta-cells, which supports a functional link between Sei1 and the core cell cycle regulators specifically in the context of the pancreas.